(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, when the ancient state of Khorezm formed and which areas it includes. Also, its ancient cities are socio-economic and economic about the life of the ancient Greek scholar about the ancient state of Khorezm,the information left by modern scientists is ancient,as a result of his scientific research on the Khorezm state, here is a brief summary of the information.